2020
DOI: 10.1029/2020gc009142
|View full text |Cite
|
Sign up to set email alerts
|

An Early Neogene—Early Quaternary Contourite Drift System on the SW Barents Sea Continental Margin, Norwegian Arctic

Abstract: Alongslope flowing ocean currents are important sediment transport agents on high-latitude continental margins at present as well as during past glacials and interglacials (e.g., Campbell & Mosher, 2016; Rebesco et al., 2014). Such currents, spatially and temporally variable, are both eroding the continental slope in areas of persistent flow strength and direction, often creating widespread unconformities, and leading to the deposition of extensive mound-shaped, elongated contourite drifts (Figure 1a) (Faugère… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 89 publications
(220 reference statements)
0
6
0
Order By: Relevance
“…The increase in mass wasting deposits related to megaslides/mass wasting may have been triggered by high sedimentation rates during the first step of glacial intensification (from ∼2.7 to 2.58 Ma), in combination with low eustatic sealevel and the presence of weak layers-contourites (Amundsen et al, 2011;Safronova et al, 2017). On the southwestern Barents Sea margin distal glaciomarine deposits prevail, interbedded with hemipelagic and/or turbiditic/contouritic deposits (e.g., Rydningen et al, 2020), cut by channels, which we relate to a glaciofluvial system developed on the shelf, in accordance with Laberg et al (2010). Apart from the northwestern Svalbard margin, we see no evidence for shelf edge glaciation on the rest of the western Svalbard-Barents Sea margin during GI period.…”
Section: Seismic Units Amentioning
confidence: 99%
“…The increase in mass wasting deposits related to megaslides/mass wasting may have been triggered by high sedimentation rates during the first step of glacial intensification (from ∼2.7 to 2.58 Ma), in combination with low eustatic sealevel and the presence of weak layers-contourites (Amundsen et al, 2011;Safronova et al, 2017). On the southwestern Barents Sea margin distal glaciomarine deposits prevail, interbedded with hemipelagic and/or turbiditic/contouritic deposits (e.g., Rydningen et al, 2020), cut by channels, which we relate to a glaciofluvial system developed on the shelf, in accordance with Laberg et al (2010). Apart from the northwestern Svalbard margin, we see no evidence for shelf edge glaciation on the rest of the western Svalbard-Barents Sea margin during GI period.…”
Section: Seismic Units Amentioning
confidence: 99%
“…Further to this, basins to the north of the Greenland Fracture Zone (Figure 1) report the presence of contourite deposits related to the opening of the Fram Strait in the Miocene (Døssing et al, 2016). However, drift sheets and other features of contourite deposition are unreported in the study area, although several contourite drifts are reported at the same latitude of the study area on the Norwegian side (e.g., Rebesco et al, 2013;Rydningen et al, 2020). Furthermore, previous studies have identified morphological characteristics of overbank deposition as indicative of turbidity current overspill, as opposed to contour current deposition (García et al, 2012).…”
Section: Glacial History and Palaeoceanographymentioning
confidence: 76%
“…6a) but later on strongly increased (see 5.4). The sediment drift in the central Fram Strait is accompanied by other, mostly younger contouritic features, like mounded drift structures and sediment waves, that were documented for the eastern vicinity of the Molloy Basin (Gebhardt et al, 2014) and elsewhere along the main flow of the WSC (Mattingsdal et al, 2014;Rebesco et al, 2013;Rydningen et al, 2020).…”
Section: Onset Of Current Controlled Sedimentation During the Tortonianmentioning
confidence: 83%